SMUGGLING OF THE LAW IN DIFFERENT RELIGIOUS MARRIAGE AS A LEGAL ACTION IN THE STATE OF PANCASILA - Arsyita, Muhammad Aprizal; Khair, Damrah; Pane, Erina; Ja'far, A. Kumedi; Mahmudah, Siti (SMART: Journal of Sharia, Traditon, and Modernity, 2021)
Marriage in Indonesia is a legal act that is valid in an external forum based on the legal contract of each religious law or belief. Interestingly, interfaith marriages continue to occur and experience problems related to illegal acts against various attempts to smuggle laws to obtain legal recognition from the State. This issue will be analyzed based on the Civil Code, Law Number 1 of 1974 concerning Marriage, Law Number 39 of 1999 concerning Human Rights, Law Number 23 of 2006 concerning Population Administration, and the Decision of the Constitutional Court Number. 68/ PUU-XII / 2014. To find out the legal arrangements in interfaith marriages, a normative juridical legal research method and a statutory approach were carried out by collecting literature study data. Secondary data were analyzed using qualitative juridical analysis. The results of this study explain that positive law in Indonesia does not prohibit interfaith marriage, but does not regulate it. The substance of the validity of a marriage is pluralistic based on religious law and belief, even though the majority prohibits its followers so that a juridical understanding emerges that it is impossible to legalize interaction marriages, but in reality, some religions and beliefs provide dispensation or permission. Law smuggling by individuals adhering to religions or beliefs with low quality and/ or not obeying the forum internum which prohibits interfaith marriages, but imposes themselves on various motives (Al-Baits) based on positive law. The conclusion is that even though there is disharmony of norms, the smuggling of law in interfaith marriages fulfills the elements of acts against the law, which deliberately contradicts positive law, and reduces the authority of law and religion in the Pancasila State. Juridically, the determination of the legality of marriage is based on religious norms or beliefs, not a Court Ruling mechanism, because the State only determines administrative validity.Keywords: Smuggling, Marriage, Different Religions, Acts against the Law, Pancasila